2022
DOI: 10.7759/cureus.30815
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis Comparing Burn Healing Outcomes Between Silver Sulfadiazine and Aloe vera

Abstract: Burn wounds remain a prevalent problem in the developed and developing world. A multitude of remedies has been tested. This study evaluated the healing time of second-and third-degree burn wounds between silver sulfadiazine (SSD) and Aloe vera (AV). In July 2020, a systematic review of MEDLINE (Ovid) and PubMed (National Library of Medicine) was performed to identify studies that reported healing of secondand third-degree burns using either SSD or AV. Articles meeting the inclusion criteria were screened and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…While research into the usefulness of L. plantarum is important, it is also critical to understand how such a treatment stacks up against similar therapies. As such, a human in vivo study compared L. plantarum to silver sulphadiazine (the gold standard for burn wound infections [ 145 , 146 ]) on PA -infected second-degree and third-degree wounds. They found that L. plantarum provided either the same efficiency or a greater efficiency than silver sulphadiazine [ 147 ].…”
Section: Probioticsmentioning
confidence: 99%
“…While research into the usefulness of L. plantarum is important, it is also critical to understand how such a treatment stacks up against similar therapies. As such, a human in vivo study compared L. plantarum to silver sulphadiazine (the gold standard for burn wound infections [ 145 , 146 ]) on PA -infected second-degree and third-degree wounds. They found that L. plantarum provided either the same efficiency or a greater efficiency than silver sulphadiazine [ 147 ].…”
Section: Probioticsmentioning
confidence: 99%
“…It is a heavy metal dermatological medication with antimicrobial effects [59,102,103]. Ag-SD has been considered the gold standard for therapeutic intervention regarding infection control of burn wounds for topical, second-and third-degree burns [62,104,105]. Ag-SD (1%) topical formulation has been reported to possess potentially good efficacy with an admirable low adverse profile for superficial and partial thickness burn [106][107][108].…”
Section: Silver Sulfadiazine (Ag-sd) In Burn Infection Controlmentioning
confidence: 99%
“…Currently, dialysis catheters use coatings such as bismuth and silver to reduce bacterial colonization and thus reduce membrane formation (14). However, due to the high cost of use and the need for further evaluation of effectiveness, it is currently not widely used (15,16). In terms of anticoagulation, anticoagulants or low-dose heparin are still used throughout the body to seal the catheter, while anticoagulant catheters are still in the research stage (17).…”
Section: Introductionmentioning
confidence: 99%